Legal Development Relating To Regulations On Education In Reducing The Number Of Social Problems In West Jawa - Indra Alika Putri, Sri; Dewi Wulansari, Catharina (CV. Inara, 2024)
This article raises the issue of the influence of educational regulations on suppressing the number of social problems in West Java, which will have implications for legal development, because one of the factors for good legal development is the small number of social problems. The focus of this research is to discuss the influence of educational regulations on reducing the number of social problems in West Java and what appropriate suggestions are for overcoming these problems. This research uses sociological juridical research where the author conducted data research and interviews with sources in their field, namely the Social Service and the West Java Province Education Service. Based on research results, educational regulations have a significant influence on reducing the number of social problems in West Java. This is because through ideal educational regulations, a good education system will be born and accommodate all levels of society to obtain both formal and informal education, so that these educational regulations have implications for controlling community behavior patterns so that they do not deviate and cause social problems in West Java.